2019
DOI: 10.1094/mpmi-03-19-0066-r
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Transcriptomic and Proteomic Analysis of Hexaploid Wheat’s Responses to Colonization by Bacillus velezensis and Gaeumannomyces graminis, Both Separately and Combined

Abstract: Tritrophic interactions involving a biocontrol agent, a pathogen, and a plant have been analyzed predominantly from the perspective of the biocontrol agent. To explore the adaptive strategies of wheat in response to beneficial, pathogenic, and combined microorganisms, we performed the first comprehensive transcriptomic, proteomic, and biochemical analysis in wheat roots after exposure to Bacillus velezensis CC09, Gaeumannomyces graminis var. tritici, and their combined colonization, respectively. The transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…A gene encoding an enzyme involved in the synthesis of abscisic acid (ABA) was found to be upregulated during G. tritici infection, suggesting that the fungus uses ABA to manipulate the host defence response [73]. The study was later extended by a transcriptomic, proteomic, and biochemical analysis of the plant response to take-all infection in the presence and absence of B. velezensis, revealing that during G. tritici infection wheat plants show a strong salicylic acid (SA)-mediated resistance response, which was stronger than the jasmonic acid (JA) accumulation response [74]. These results contradict the role of JA in plant defence observed during pathogen infections of leaves, confirming previous observations that defence signalling in roots cannot be extrapolated from research on leaves [75].…”
Section: Molecular Interactions Between G Tritici and Wheatmentioning
confidence: 99%
“…A gene encoding an enzyme involved in the synthesis of abscisic acid (ABA) was found to be upregulated during G. tritici infection, suggesting that the fungus uses ABA to manipulate the host defence response [73]. The study was later extended by a transcriptomic, proteomic, and biochemical analysis of the plant response to take-all infection in the presence and absence of B. velezensis, revealing that during G. tritici infection wheat plants show a strong salicylic acid (SA)-mediated resistance response, which was stronger than the jasmonic acid (JA) accumulation response [74]. These results contradict the role of JA in plant defence observed during pathogen infections of leaves, confirming previous observations that defence signalling in roots cannot be extrapolated from research on leaves [75].…”
Section: Molecular Interactions Between G Tritici and Wheatmentioning
confidence: 99%
“…Unique, 14-3-3 proteins are phosphate-binding proteins carbohydrate metabolism, cellular processes, protein metabolism, and sugar metabolism. These main metabolic processes were also identified in soybean root diseases, Chinese cabbage, and wheat (Bai et al, 2019;Kang et al, 2019;Lan et al, 2019). Carbohydrate metabolism, cellular processes, energy and protein metabolisms, signalling, and stress response were higher in asymptomatic seedlings.…”
Section: Proteins In Roots Of Symptomatic and Asymptomatic Seedlingsmentioning
confidence: 95%
“…Bacillus cereus 0-9 is a highly adaptable bacterium that is widely distributed in soil, water, plants, and wheat rhizospheres (Kang et al, 2019). Our previous study showed that the wild-type B. cereus 0-9 isolates can form pellicles on air-liquid interfaces and architecturally complex colonies on solid surfaces (Zhang et al, 2020a).…”
Section: Biofilm Formationmentioning
confidence: 99%